1991
DOI: 10.1084/jem.173.5.1159
|View full text |Cite
|
Sign up to set email alerts
|

The C3b/C4b receptor is recognized by the Knops, McCoy, Swain-langley, and York blood group antisera.

Abstract: SummaryErythrocytes (E) lacking high incidence blood group antigens were screened by an antiglobulin test with a monoclonal antibody to human complement receptor type 1 (CR1 ; C3b/C4b receptor; CD35) . Some examples of E lacking Knops, McCoy, Swain-Langley, and York antigens, a serologically related group, were not agglutinated . Moreover, E of the null phenotype for these same antigens were nonreactive. To further explore this relationship, E expressing these antigens were surface labeled, solubilized, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 17 publications
1
72
0
Order By: Relevance
“…Knops-McCoy blood group antiserum, which is specific for CR1, served as a positive control. 32 Positive patient samples were confirmed specific for sCR1 by preincubating with excess sCR1 and rerunning the assay.…”
Section: Immunogenicity Assaysmentioning
confidence: 99%
“…Knops-McCoy blood group antiserum, which is specific for CR1, served as a positive control. 32 Positive patient samples were confirmed specific for sCR1 by preincubating with excess sCR1 and rerunning the assay.…”
Section: Immunogenicity Assaysmentioning
confidence: 99%
“…[6][7][8] In 1991, two groups independently identified the Knops blood group system on CR1. 9,10 It has been shown to be independent from the other known CR1 polymorphisms, ie, molecular weight or red cell expression. The Knops blood group system began with the description of anti-Knops (Kn a ), in a transfused Caucasian woman.…”
Section: Introductionmentioning
confidence: 99%
“…Another European study, which used only RFLP analysis, also found an increase of the CR1-B allele [17]. However, the latter was performed before the Knops-CR1 blood group was found [25], and it is unknown whether the RFLP actually correlates with one of the blood group specificities and not with CR1 size.…”
Section: Discussionmentioning
confidence: 99%